Pedofilia w polskim Kościele rzymskokatolickim jako jeden z wiodących problemów społecznych w kampaniach wyborczych w 2019 r. - Płachecka, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to characterize the problem of pedophilia in the Polish Roman Catholic Church as one of the leading social problems, which, appearing during the campaign for the European Parliament and the subsequent parliamentary campaign in 2019, also took on a strongly political dimension. The article takes up the challenge of answering the question of what was the position of the leaders of individual political parties on the problem of pedophilia in the Polish Roman Catholic Church during the campaign competition in 2019 and what level of agency the public debate on this problem in 2019 achieved.
Keywords: Kościół Rzymskokatolicki; Konferencja Episkopatu Polski; kampania wyborcza; Watykan; pedofilia; PKPD; Roman Catholic Church; Polish Episcopal Conference; election campaign; Vatican City State; pedophilia